CSR practice at energy sector procurement in Bangladesh: a case study on gas transmission pipeline project under Gas Transmission Company Ltd.(GTCL) - Faroque, Iqbal Bahar (BRAC Univeristy, 2018)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2018.